Proceedings of the 5th IPMA SENET Project Management Conference (SENET 2019) 2019
DOI: 10.2991/senet-19.2019.41
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digitalisation on the organisational capability changes – Evidence from Serbia

Abstract: Business across all industries had been influenced by the rise of digitalisation trends. This had provided an imperative for organisations to change in order to remain competitive in the marketplace. Companies had to transform an organisation behaviour, process, or culture in the way which reflected the new business opportunities in digital environment. The following study analyses the implications of digital transformation in the companies located in Serbia, by highlighting the several dimensions of its multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The revolution of ICT has changed the roots of the nature of business by providing instant access to information which necessitates infrastructural changes and technological developments to adapt to the new wave of business operations [38]. The study revealed that South African organisations within the telecommunications industry must have capable and inclusive infrastructure to support mobile technology initiatives and have mobile platforms that are compatible.…”
Section: Technological Readinessmentioning
confidence: 99%
“…The revolution of ICT has changed the roots of the nature of business by providing instant access to information which necessitates infrastructural changes and technological developments to adapt to the new wave of business operations [38]. The study revealed that South African organisations within the telecommunications industry must have capable and inclusive infrastructure to support mobile technology initiatives and have mobile platforms that are compatible.…”
Section: Technological Readinessmentioning
confidence: 99%
“…In order to follow the development trend of the observed research topic (Roth et al, 2020) or trends (Zhu et al 2020), journal publication activity (Tang et al, 2018) or scientific discipline (Lampe et al, 2020) the authors have recognized benefits of bibliographic analysis for greater comprehension of activities performed in the scientific community. Complex bibliographic data and metadata provide a wide range of analytical possibilities, which represents one of potentials of digital transformed organizational capacity (Slavinski and Todorovic, 2019). The application of IT technologies has led to fundamental changes in the field of librarianship (Salazar 2019).…”
Section: Introductionmentioning
confidence: 99%